Jakob der Lügner [videorecording (DVD)] - Beyer, Frank, 1932-2006; Brodský, Vlastimil; Mueller-Stahl, Armin, 1930-; Geschonneck, Erwin, 1906-2008; Hübchen, Henry, 1947-; Kommerell, Blanche; Kasten, Ullrich; Schenk, Ralf, 1956- (Icestorm International, 1999)
Trapped in a Polish ghetto with thousands of other Jews facing starvation or deportation to the death camps, Jacob is detained one evening at the local Gestapo headquarters. Eavesdropping, he overhears a radio report about a nearby Russian victory. At first he is silent, but circumstances compel him to pass on the good news of hope. A simple, somewhat dour man, the stubble-bearded Jacob suddenly becomes a hero as old friends and neighbors flock to him, pressing for information about the latest reports. Jacob feels compelled to make up stories to keep up the spirits of his comrades.